2017
DOI: 10.1007/s11999-017-5433-3
|View full text |Cite|
|
Sign up to set email alerts
|

Does Postoperative Glenoid Retroversion Affect the 2-Year Clinical and Radiographic Outcomes for Total Shoulder Arthroplasty?

Abstract: Level III, therapeutic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 66 publications
0
22
0
Order By: Relevance
“…A total of 25 studies were noncomparative. Of these studies, 9 examined keeled glenoid fixations9, 12, 15, 19, 23, 31, 50, 51, 54 and 16 examined pegged glenoid fixations5, 7, 14, 25, 26, 27, 28, 29, 35, 36, 38, 39, 42, 45, 49, 53 (Table I). Among these studies, 10 reported ASES scores, 16 reported Constant scores, 19 reported radiolucency rates, and 19 reported revision rates.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 25 studies were noncomparative. Of these studies, 9 examined keeled glenoid fixations9, 12, 15, 19, 23, 31, 50, 51, 54 and 16 examined pegged glenoid fixations5, 7, 14, 25, 26, 27, 28, 29, 35, 36, 38, 39, 42, 45, 49, 53 (Table I). Among these studies, 10 reported ASES scores, 16 reported Constant scores, 19 reported radiolucency rates, and 19 reported revision rates.…”
Section: Resultsmentioning
confidence: 99%
“…There could be bias between the study group and patients lost to follow-up, but our follow-up rate is comparable to other studies. 16 , 31 Third, our mean follow-up is 4.2 years, though the TSA survival is expected to exceed 10 years. Longer follow-up is needed to provide more information on the relationship between radiographic measures, clinical outcomes, and implant longevity.…”
Section: Discussionmentioning
confidence: 96%
“…There was no significant difference between the 2 groups in outcomes at 2-year follow-up. 31 Recent reports using CT scans to evaluate preoperative glenoid retroversion have also shown no clinical differences. 4 We observed that the change in retroversion was not associated with better clinical outcomes and that final clinical outcomes were not dependent on postoperative glenoid retroversion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations